Steganography Formation by utilizing Enhanced Least Significant Bit Algorithm - Pristiwanto, Pristiwanto; Abdul Halim Hasugian (Jurnal Info Sains : Informatika dan Sains, 2021)
Steganography is the science and art of hiding secret messages in other messages so that the existence of those messages cannot be known. The letter sent does not attract attention with steganography, and the container media does not arouse suspicion. Steganography requires two properties, namely container media and secret messages. The LSB method (least significant bit)is the simplest and easiest steganography method to implement. An example of implementing this method is to use a digital image as a cover text. Each pixel in the image is 1 (one) to 3 (three) bytes in size. Pda bit arrangement in a byte ( 1 byte = 8 bits), there are the most significant bits ( MSB) and the least significant bits (LSB). For example, on 11010010 bytes, the first bit from the right is the MSB bit, and the last bit from the right is the LSB bit. The matching bit is replaced with the message bit is the LSB bit, because the modification only changes the byte value to one higher or one lower than the previous value